Member States in the EU Research and Innovation Framework Programmes - Bērziņa, Dina (International Journal of Engineering and Technology, 2018)
Sustainable growth is the key driver of development and it depends on research and innovation which creates investment opportunities for new and better products and services and thereby increases the competitiveness and employment. Research has a long history on our old continent: the European Union is a research think-tank, still the world’s leading producer of scientific knowledge but is lagging in implementation of the results. Therefore, constitution of the Framework Programmes enabled better coordination of research among all the participating countries. The EU Framework Programmes celebrated 30 years of operation recently – they have become a key element of the research policy in Europe today. Since the First Framework Programme launched in 1984, the current Horizon 2020 has expanded in scope and scale by attracting more resources and participating countries performing research on diverse topics. This paper provides an overview of the EU Member States’ engagement with emphasis on the two last Framework Programmes. It outlines the current disproportion with respect to different country group performance and provides links to various data sources for further studies.